2012
DOI: 10.1111/pbi.12002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of sugars and simple sugar derivatives in plants

Abstract: SummaryCarbon captured through photosynthesis is transported, and sometimes stored in plants, as sugar. All organic compounds in plants trace to carbon from sugars, so sugar metabolism is highly regulated and integrated with development. Sugars stored by plants are important to humans as foods and as renewable feedstocks for industrial conversion to biofuels and biomaterials. For some purposes, sugars have advantages over polymers including starches, cellulose or storage lipids. This review considers progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 197 publications
(261 reference statements)
4
137
0
8
Order By: Relevance
“…In the stem storage parenchyma cells, ZmSUT1 may function to take up Suc from the apoplasm during expansive growth and to retrieve Suc leaked from cells during accumulation and to maintain turgor. A similar function has been proposed during sugar accumulation in sugarcane and sweet sorghum (Sorghum bicolor) stems (Bihmidine et al, 2013Patrick et al, 2013). pZmSut1::RFPer also was expressed in the region of the release phloem, which was marked by symplasmic CF unloading into the developing leaves and roots.…”
Section: Function Of Zmsut1 In Nonconducting Cells Within Source Tissuesupporting
confidence: 64%
“…In the stem storage parenchyma cells, ZmSUT1 may function to take up Suc from the apoplasm during expansive growth and to retrieve Suc leaked from cells during accumulation and to maintain turgor. A similar function has been proposed during sugar accumulation in sugarcane and sweet sorghum (Sorghum bicolor) stems (Bihmidine et al, 2013Patrick et al, 2013). pZmSut1::RFPer also was expressed in the region of the release phloem, which was marked by symplasmic CF unloading into the developing leaves and roots.…”
Section: Function Of Zmsut1 In Nonconducting Cells Within Source Tissuesupporting
confidence: 64%
“…[1][2][3][4][5] Multiple crops have been independently bred to store high concentrations of sucrose in terminal storage organs, namely, the taproots of sugar beet (Beta vulgaris L.), and the stems of sweet sorghum (Sorghum bicolor L. Moench) and sugarcane (Saccharum officinarum L.). [5][6][7][8][9] However, the sucrose contents of these crops appear to be approaching maximal levels attainable from breeding efforts 10,11 ; therefore, new approaches are needed to increase sucrose accumulation in storage organs. Hence, characterizing the genes that function in sucrose transport and storage will reveal potential new targets for future manipulations to enhance crop yields.…”
mentioning
confidence: 99%
“…Sáez et al (2012) reported that in C. sativa, the chloroplasts of plantlets that had been grown in vitro were devoid of starch, probably because of a low photosynthetic activity or because exogenous sucrose created negative feedback on the enzymes in the plastids that are responsible for starch biosynthesis. However, it should be emphasized that starch accumulation also depends on its degradation rate in sink heterotrophic organs (Patrick et al 2013). In addition, low plastoglobulus content under in vitro conditions may result in a low capacity of in vitro plantlets to prevent oxidative damage in the membrane systems of chloroplasts.…”
Section: Discussionmentioning
confidence: 99%